Optimalisasi Digital Marketing Bagi Generasi Z Dalam Pengembangan Pemasaran Berbasis Teknologi - Valian Yoga Pudya Ardhana; M. Dermawan Mulyodiputro; Lilik Hidayati (Puslitbang Akademi Relawan TIK Indonesia (ARTIKA), 2023)
The role of technology in electronic advertising is known as digital marketing, while creating a company's image is known as digital branding. Digital marketing is an evolution of product marketing that can be triggered by technology such as websites, cell phones, and even games. Social media can be understood as one of the online media where users can easily participate, such as sharing created content, sharing and creating stories, expanding networks, wiki channels, forums, and virtual worlds. In this way, digital marketing methods to promote a brand or product are more effective and spread quickly. At the same time, tactics and communication are also very necessary in marketing. Generation Z, the young generation of productive age, has a very important role in implementing product marketing. This young generation is a young generation who is creative and innovative and sensitive to developments in life, so the role of Generation Z in efforts to develop digital marketing technology is very important. The results of this community service will help improve the skills of Generation Z on Lombok Island. Digital marketing skills to develop product marketing and promotions.